2019
DOI: 10.1177/1024907919851999
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year retrospective review of stonefish sting injury in Hong Kong

Abstract: Background: Stonefish sting injury is one of the common marine stings in Hong Kong. It is commonly sustained during maritime activities, and it could be regarded as occupational hazard for chefs or domestic hazard for family. Its envenomation could lead to significant local symptoms (pain or swelling) and serious complications, including infection and compartment syndrome. Objectives: This study is to review its clinical presentation and various treatment modalities. Methodology and study design: Reported case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…In a report released by the Hong Kong Poison Information Center, a total of 32 cases were observed during a 10-year period. 5 Thus, the annual number of stonefish envenomation cases in the current study was similar to that reported in Hong Kong. However, a hospital in Singapore reported 30 cases during a 2-year observation period 2 (i.e., five-fold higher incidence versus that reported in Japan).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a report released by the Hong Kong Poison Information Center, a total of 32 cases were observed during a 10-year period. 5 Thus, the annual number of stonefish envenomation cases in the current study was similar to that reported in Hong Kong. However, a hospital in Singapore reported 30 cases during a 2-year observation period 2 (i.e., five-fold higher incidence versus that reported in Japan).…”
Section: Discussionsupporting
confidence: 85%
“…12 In the study undertaken in Hong Kong, 25% of patients received treatment with antivenom. 5 The only commercially available fish antivenom is the stonefish antivenom produced by CSL (Melbourne, Australia). This antivenom consists of the purified F(ab)2 fragment of equine immunoglobulin G antibodies raised against the venom of S. trachynis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiology: Stonefish stings, including those from reef stonefish, are a common injury seen in the emergency room. They are primarily found in the coastal waters of the Indo-Pacific region, including the USA, Australia, Malaysia, Hong Kong, and Singapore [17][18][19][20][21]. Few Japanese studies of stonefish envenomation have been reported [22,23]; however, Hifumi et al recently reported 15 cases over a 5-year observation period [24] and two deaths related to stonefish envenomation have been reported in Japan [25].…”
Section: Stonefishmentioning
confidence: 99%
“…Antivenom is available and consists of the purified F(ab)2 fragment of equine IgG antibodies raised against the venom of Synanceia trachynis [26]. In a study conducted in Hong Kong, 25% of patients received treatment with antivenom [21].…”
Section: Stonefishmentioning
confidence: 99%